The institutional memory hypothesis and the procyclicality of bank lending behavior - Berger, Allen N.; Udell, Gregory F. (Journal of Financial Intermediation, 2004)
We test a new hypothesis that may help explain the procyclicality of bank lending. The institutional memory hypothesis is driven by deterioration in the ability of loan officers over the bank's lending cycle that results in an easing of credit standards. We test this hypothesis using data from individual US banks over 1980–2000: over 200,000 bank-level observations on commercial loan growth, over 2,000,000 loan-level observations on interest rate premiums, and over 2000 bank-level observations on credit standards and loan spreads from bank management survey responses. The empirical analysis supports the hypothesis, although there are differences by bank size class.